Mechanistic insight into the regulation of SQSTM1/p62. Issue 4 (3rd April 2019) - Zhang, Yi; Mun, Su Ran; Linares, Juan F.; Towers, Christina G.; Thorburn, Andrew; Diaz-Meco, Maria T.; Kwon, Yong Tae; Kutateladze, Tatiana G.
ABSTRACT: SQSTM1/p62 facilitates responses to various cellular stresses and has been implicated in human diseases. This protein functions as a major cytoplasmic signaling hub and has multiple binding partners, including arginylated (Nt-R) proteins that are recognized by the ZZ domain of SQSTM1/p62 (SQSTM1/p62ZZ ). We have determined the molecular mechanism of Nt-R recognition using a combination of biochemical and NMR approaches and obtained the crystal structure of SQSTM1/p62ZZ in complex with Nt-R. We found that binding of SQSTM1/p62ZZ to Nt-R induces SQSTM1/p62 puncta formation and macroautophagy/autophagy and identified a regulatory linker (RL) region of SQSTM1/p62 that associates with SQSTM1/p62ZZ in vitro . Our findings suggest a mechanism for SQSTM1/p62 autoregulation that can be essential in mediating autophagy.